Skull base osteomyelitis presenting with an isolated hypoglossal nerve palsy. (12th July 2013) - Kasfiki, Eirini Vasileiou; Kelly, Ciaran; Smith, John; Nicolaides, Andreas
Abstract : This is the first case of skull base osteomyelitis presenting with isolated bilateral hypoglossal nerve palsy reported in the literature. A 75-year-old man presented with tongue paralysis without any other cranial nerve palsy. He was otherwise well apart from recently having a high prostate-specific antigen level recorded. Investigations for malignancy or cerebrovascular insult were negative with the diagnosis of skull base osteomyelitis confirmed using CT. Following treatment with intravenous antibiotics for 6 weeks, symptoms resolved.